Social Media Utilization for Student Learning Success Effectiveness - Karina, Dwivedi; Rishi, Prasad; Rashmi, Giri (World Psychology, 2023)
Teachers teach at school using a variety of media, one of which is social media which has a positive and negative impact on students. Many students are lazy to learn because they have been facilitated by the current media and supported by teachers who use social media in teaching. Not a few of the students who abuse the use of social media, such as seeing things that are inappropriate for students to see, so that it greatly affects student learning achievement. The purpose of this study is that students can know and utilize social media as a learning resource so that learning can be effective for the success of student learning itself. This research uses quantitative methods, by means of interviews and analysis. The interview here is conducted online using social media to one of the students at the school, namely whatsaap, after which it is analyzed. The results of this study are expected to provide an understanding to students how to utilize social media so that learning by teachers and students can be effective and produce satisfactory grades. The conclusion of this study shows that social media must be utilized properly supported by teacher guidance so that student learning objectives can be achieved optimally. Therefore, the limitations of this study are that researchers only conduct research that examines the problem of utilizing social media for the effectiveness of student success, researchers hope that future researchers can conduct research by developing the discussion of this research to the fullest